IMPACT OF COST OF LIVING, LEARNING, SOCIAL ENGAGEMENT AND ACADEMIC PERFORMANCE ON WELL-BEING OF B40 UiTM STUDENTS - Sakinah Binti Mat Zin,; Roseliza Binti Hamid,; Nurul Syaqirah Bte Zulqernain,; Noorazzila Binti Shamsuddin,; Nik Sarina Binti Nik Md Salleh, (Journal of Islamic, Social, Economics and Development, 2023)
The purpose of this paper is to empirically investigate behavioural and contextual impact of cost of living, learning, social engagement and academic performance on well-being of B40 UiTM students. A quantitative method was used by utilizing the correlation method to scrutinize the dissimilarities of study sample characteristics and examine which variables are connected. Also, questionnaires are used to gather information from respondents. The study objectives are to identify the level of well-being, to identify the statistically significant differences of gender and family background and also to identify the influence of cost of living, learning, social engagement and academic performance on the well-being of B40 UiTM students. This study contributes to the literature on well-being among B40 UiTM students by assessing the main variable impact on it.